How to legitimate the European Union and the integration process: EU governance approach - Volodin, Dmytro (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2011)
This article addresses and responds to the question of changes in the European Union governance and how we can legitimate the process of European integration according to internal facilities. Some of the main conclusions refer to the lack of institutions capable of performing their functions as well as the key elements for achieving possible changes towards democracy.